De la conciencia del linaje a la defensa estamental. Acerca de algunas narrativas nobiliarias vascas - Arsenio Dacosta (Medievalista)
The purpose of this paper is to analyze a set of origin narratives concerning the nobility of the Manor of Biscay and its environment in the Middle Ages. First, the set of legends around the House of Haro, holder of the manor for several centuries, which were first transmitted by the Portuguese chronicler Pedro Afonso, count of Barcelos. Second, we analyze the origin narratives of the Lords of Ayala, collected and updated by Fernán Pérez, father of the famous Chancellor Ayala. Finally, we present several examples of genealogical mystification related to the land’s lower nobility as transmitted by Lope García de Salazar. Our analysis involves a twofold constructivist perspective: first by showing that nobility mythomania is actively constructed by nobility itself; secondly, in the sense that this construction is adaptive. Such narratives are by their own nature identitarian and have an excluding value which is limited to the lineage itself, which is another instance of intra-manorial competition in the late Middle Ages. But at the same time, they build an elaborate estate discourse which, in each analyzed author, contains different nuances which are closely linked to each specific historical context.